Development of a Dark Matter Detector that Uses Liquid He and Field Ionization. (February 2020) - Osterman, D; Maris, H; Seidel, G; Stein, D
Abstract: We describe a new detector capable of directly measuring dark matter particles with masses as low as 1 MeV/ c 2 . The detector is based on the quantum evaporation of helium atoms from the surface of liquid helium and their detection using field ionization. When a dark matter particle collides with an atom in liquid helium, the deposited energy results in the evaporation of helium atoms from the liquid surface. A dense array of sharp, positively charged metal tips, known as the field ionization detector array, creates a strong electric field that ionizes the helium atoms and accelerates them into a calorimeter, which detects the impact. We studied field ionization from single tips and investigated the dependence of the ionization rate on the applied voltage. We discuss the results of these single tip field ionization experiments, as well as upcoming experiments, which will focus on studying the temperature dependence of field ionization of gaseous helium at low temperatures.